Analisis Semiotika pada Konten Komedi Bintang Emon Terkait Gaya Politik Pemerintah Indonesia Melalui Instagram @Bintangemon - Rosemelba, Jessica; Yunita Indinabila (LPPM Stikosa-AWS, 2024)
This study focuses on the way Bintang Emon convey socio-political criticism through comedy on social media, especially Instagram. Using Charles Sanders Peirce's semiotic analysis method, this study examines the use of signs and meanings in one of Bintang Emon's Comedy content that alludes to political issues related to the House of Representatives. The results revealed that humor and satire in the content of Bintang Emon were effective in shaping people's perception of the government's political style. The content is not only entertaining but also invites the audience to think critically about the political reality in Indonesia. The research provides new insights into the role of comedy as a tool of social control and social media as a platform for political communication.